Advertising of unhealthy foods and beverages around primary and junior high schools in Ghana's most urbanized and populous region - Amevinya, Gideon Senyo; Vandevijvere, Stefanie; Kelly, Bridget; Afagbedzi, Seth Kwaku; Aryeetey, Richmond; Adjei, Akosua Pokua; Quarpong, Wilhemina; Tandoh, Akua; Nanema, Silver; Agyemang, Charles; Zotor, Francis; Laar, Matilda E.; et al. (Frontiers in Public Health, 2022)
Introduction: The advertising of energy-dense, nutrient-poor foods and beverages is a common feature in obesogenic food environments. Such advertising, within and around settings where children live, learn, and play, negatively affects their food acquisition and consumption. We examined the extent and nature of food and beverage advertising around primary and junior high schools in Ghana’s most populous and urbanized region, Greater Accra. Materials and Methods: Outdoor advertisements for foods and beverages within a 250m road network distance of 200 randomly sampled schools were geocoded. For each food and beverage advertisement, information was collected on the setting, type, size, and number of product types featured in the advertisement. Promotional techniques (promotional characters and premium offers) used in advertisements were documented. Advertised foods and beverages were classified using the INFORMAS and NOVA food classification systems. Results: A total of 5,887 advertisements were identified around the schools surveyed, 42% of which were for foods and beverages. Advertisements were most prevalent at food outlets (78% of all food advertisements), but also along roads and on non-food structures. Overall, 70% of food advertisements featured non-core/unhealthy products, while 12% and 14% had core/healthy and miscellaneous (including soup cubes, seasonings, and tea) products. About 4% of food advertisements had only a product/brand name or logo displayed. One out of two of the foods and beverages advertised were ultra-processed foods, 30% processed, 3% processed culinary ingredients, and 17% unprocessed or minimally processed foods. Sugar-sweetened beverages were the most advertised food product type (32%). Promotional characters were found on 14% of all food advertisements (most–69% were cartoons or manufacturer’s characters), while 8% of all food advertisements had premium offers (including price discounts and gift/collectables). Conclusions: There is an abundance of unhealthy food advertisements around primary and junior high schools in the Greater Accra Region. Policy actions such as restricting the promotion of unhealthy foods in children’s settings are needed to protect pupils from such advertising practices.